The influence of digital competence on generation z's political participation in the city of Jayapura - Iriando Wijaya; Fanny K. T. Sitompul; Leon M. Harju; Musa K. Payokwa; Wilhelmina A. Insoraky (Tamalanrea: Journal of Government and Development (JGD), 2024)
This study explores the impact of digital competence on political participation among Generation Z in Jayapura City. Using a quantitative approach, the research surveyed 250 Gen Z respondents aged 17–28, selected through purposive sampling. Data collection was conducted via surveys and analyzed using correlation and regression methods. The findings reveal significant effects of three core aspects of digital competence on political participation: digital knowledge (R² = 0.228, p < 0.05), digital ability (R² = 0.658, p < 0.05), and digital behavior (R² = 0.396, p < 0.05). Despite exhibiting high levels of digital competence, Generation Z's political participation remains low. This indicates a noticeable gap between their advanced digital proficiency and their limited active engagement in political activities. The study concludes that while digital competence significantly influences political participation, it does not necessarily translate into increased active involvement among Generation Z in Jayapura City. These findings highlight the challenges in leveraging digital potential to enhance political engagement among young voters and emphasize the need for strategies that bridge this gap.